Feasibility of Canva Application-assisted Ladder Snake Game on Basic Elements of Branding and Marketing - Kusumaningtias, Berliana Gita; Widowati, Widowati (Universitas Negeri Semarang, 2025)
This study aims to assess the feasibility of learning media for the Canva application-based Snakes and Ladders game on the Basics of Branding and Marketing elements in the Fashion Cosmetology skills program at SMK. The need for interactive and contextual learning media is the basis of this research, considering that learning is still dominated by conventional methods that do not encourage student involvement. The research method used a quantitative descriptive approach with expert validation, involving five media experts and six material experts. The assessment instrument was a 4-point Likert scale questionnaire measuring visual aspects, readability, functionality, content suitability, language, and relevance. Proof of content validity using Aiken's V with 5 raters obtained a result of≥ 0. 87 and declared all instrument items valid. Reliability estimation using Intraclass Correlation Coefficient (ICC) obtained a result of≥ 0. 87 with the criteria that the instrument has good reliability. Media feasibility was analyzed using descriptive percentage. The results showed that media experts gave a score of 89, 17% while material experts gave a score of 91, 67%. The media is considered suitable for use after minor improvements, such as improving visual readability, integrating interactive QR codes, mapping game boxes to learning outcomes, and providing a glossary. This media has the potential to increase student engagement, facilitate collaborative learning, and can be adapted for various other areas of expertise in SMK.